Prevalence of hepatitis among young men who have sex with men and transgender women in Brazil - Carina Carvalho dos Santos; Beo Oliveira Leite; Fernanda Washington de Mendonça Lima; Laio Magno; Alexandre Grangeiro; Mateus Westin; Daniel Lima de Moura; Inês Dourado (Universidade de São Paulo, 2024)
ABSTRACT OBJECTIVE: Viral hepatitis and sexually transmitted infections disproportionally affect men who have sex with men (MSM) and transgender women (TGW). However, only a few studies have evaluated the prevalence of hepatitis in these populations, especially in youths and adolescents. This study aimed to estimate the prevalence of biomarkers for hepatitis A, B, and C among young and adolescent MSM and TGW in three Brazilian municipalities. METHODS: Baseline data were collected from a combination of HIV prevention cohort of young and adolescent MSM (AMSM) and TGW (ATGW) aged 15-19 years in three Brazilian municipalities. A social behavioral questionnaire was applied, and immunoassays were performed to detect antibodies against hepatitis A (anti- HAV IgG and IgM), hepatitis B (anti-HBc and anti-HBs), and hepatitis C virus (anti-HCV); testing for the active hepatitis B marker, HBsAg, was also performed. The prevalence of reactive tests and 95% confidence interval (CI) for proportions were measured. RESULTS: The prevalence of naturally or artificially acquired immunity for hepatitis A totaled 17.7% (95%CI: 15.4-20.4), whereas that of acute infection, 0.4% (95%CI: 0.2-1.2). For hepatitis B and C, prevalence rates totaled 2.8% (95%CI: 1.8-4.4) and 0.2% (95%CI: 0.1-1.1), respectively. About 25.7% (95%CI: 22.4-29.4) of participants were non-reactive for anti-HBc and reactive for anti-HBs, the latter being a vaccine marker for hepatitis B. CONCLUSIONS: The investigation of viral hepatitis biomarkers among vulnerable populations enables the early identification of infections, the provision of timely treatment, and an opportunity to point out the need to expand vaccination coverage.